Cultural and legal hybridism: in search of a new legal theory for the regulation of informational phenomena - Veronese, Alexandre (UNIO – EU Law Journal, 2025)
This study is a theoretical exploration of the limitations of legal theory when addressing informational phenomena. It begins by observing that sociology and communication sciences already offer frameworks for understanding the intersection between social and digital life. However, this intersection has become increasingly problematic with the radical intensification of connectivity. The research employs an abstract analysis of ideal models of Internet regulation and their interplay with user behavior. It presents a detailed framework, outlining classical types of regulation and evaluating the extent to which these normative orders are adhered to on a continuum ranging from minimal to maximal compliance. The latter section critically assesses various legal theories. A key finding is that all these theories rely on the nation-state as a central element in defining the essence of Law. Further, the study examines theoretical approaches to overcoming this limitation. These include proposals to open national legal systems to external and reciprocal influences, promote legal harmonisation, and develop a concept of transnational legal pluralism. The work introduces the idea of legal norms and rules as cultural and legal hybrids, borrowing from anthropology to address the complex interplay between social and digital life. It concludes that while opening national legal systems to external influences offers significant potential, this approach also risks undermining fundamental principles of the rule of law.